Impacto del COVID 19 en la implantación de las Tic en los alumnos de Maestría en Gestión Pública promoción XV de la UNAP 2021 - Macedo Dominguez, Cesar Augusto (2024)
The main objective of this thesis report was to identify the impact of the Covid 19 on the implementation of ICT in the students of the master's degree in public management, promotion XV of the UNAP 2021. Opting for a basic study of explanatory level and design non-experimental, taking as the population 60 students from the G.P master's degree faculty, who were surveyed through a questionnaire to collect information. According to the results obtained, the report concluded that there is a positive impact of the Covid 19 Pandemic on the implementation of ICT, since the adaptation to new technologies to a large extent (75.8%) has been motivated by the restrictions established since the pandemic. Likewise, the positive impact of the perception of the severity of Covid 19 on the implementation of ICT was demonstrated since the result was statistically significant (0.000). Furthermore, it was determined that there is a positive impact of the perception of the controllability of Covid 19 on the implementation of ICT, since the latter is explained by 57.6% of the measures to control the spread of the virus. On the other hand, security measures had a positive impact on the implementation of ICT, since any provision to promote people's safety, such as distancing, as well as using alternative means for communication, in this case virtuality has explained the implementation of ICTs by 67%. Finally, there is a positive impact of knowledge of Covid 19 on the implementation of ICT, since by knowing everything related to the virus, students have had to adapt to the technological era to develop their work and academic activities.